PERAN PENGASUH DALAM PERKEMBANGAN SOSIAL PADA ANAK PANTI ASUHAN AMALIAH TEBING TINGGI - Rebecca Eka Christy Manurung; Vidya Zati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of caregivers in the social development of children at Amaliah Orphanage Tebing Tinggi. Social development is an important aspect in shaping children's personality and social interaction skills. Children living in orphanages require guidance and care that can support their social growth and emotional well-being. This study used a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The subjects of this study consisted of caregivers and foster children at Amaliah Orphanage Tebing Tinggi. The results showed that caregivers have an important role in fulfilling children’s basic needs, providing guidance, instilling discipline, motivating children, and shaping positive character. Caregivers also act as substitute parents who provide affection, attention, and emotional support to foster children. The social development of children in the orphanage is reflected through the ability to interact, cooperate, adapt, and build confidence in social environments. Supporting factors include the existence of religious and educational activities, while inhibiting factors include limited caregivers and restricted social interaction outside the orphanage environment. Therefore, caregivers are expected to improve the quality of guidance and provide more social activities to support children's social development. Keywords: caregiver role, social development, foster children